2000
DOI: 10.1080/09540120047468
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural factors associated with HIV seroconversion in homosexual men attending a central London STD clinic: A feasibility study

Abstract: An unmatched retrospective case control study was conducted to test the feasibility of investigating social and behavioural factors which may have contributed to recent HIV seroconversion in a group of homosexual men. Participants, recruited from a London sexually transmitted disease (STD) clinic, were sexually active and had had a negative HIV test with a subsequent test (positive (cases) or negative (controls)) within three to 15 months. Twenty cases and 22 controls were recruited between February and Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
0
12
0
3
Order By: Relevance
“…Negotiated safety is not risk-free: partners can violate the agreement (Davidovich et al, 2000;Guzman et al, 2004) and condom misuse may lead to slippage or breakage (e.g., Warner et al, 2008). Nonetheless, this strategy can help to prevent transmission of STDs and HIV (Gilbart et al, 2000). Negotiated safety was an implicit strategy cited in statements by men in our sample who discussed having an "understanding" with their sex partners, in which they agreed that they would not use a condom in their primary relationship, but it was not clear how explicit these understandings were.…”
Section: Discussionmentioning
confidence: 99%
“…Negotiated safety is not risk-free: partners can violate the agreement (Davidovich et al, 2000;Guzman et al, 2004) and condom misuse may lead to slippage or breakage (e.g., Warner et al, 2008). Nonetheless, this strategy can help to prevent transmission of STDs and HIV (Gilbart et al, 2000). Negotiated safety was an implicit strategy cited in statements by men in our sample who discussed having an "understanding" with their sex partners, in which they agreed that they would not use a condom in their primary relationship, but it was not clear how explicit these understandings were.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study investigating the social and behavioural factors contributing to HIV seroconversion (Gilbart et al ., 2000) included a request to participants to give an 'account of factors they personally felt were important in contributing to their subsequent seroconversion' (p. 51). The study participants, homosexual men, cited emotional issues and the use of drugs and alcohol as contributing to their seroconversion.…”
Section: Discourses Of Riskmentioning
confidence: 99%
“…Alcohol abuse and human immunodeficiency virus (HIV) infection are major public health problems in the United States and throughout the world (Karon et al., ; Stinson et al., ). Several studies have shown an association between alcohol consumption and the risk of becoming infected with HIV (Gilbart et al., ; Kalichman et al., ; Semple et al., ; Simbayi et al., ). The incidence of alcohol abuse among HIV‐infected individuals is greater than the population as a whole (Lefevre et al., ; Miguez et al., ).…”
mentioning
confidence: 99%